IMPLEMENTASI SELF DETERMINATION PRINCIPLE TERHADAP SUKUBANGSA DALAM BENTUK INTERNAL RIGHTS SELF DETERMINATION - Harita, Suluhsy Luhur; Deliana, Evi; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The right to self-determination is regulated in Article 1 paragraph (2),Article 55, Article 73 and Article 76 of the Charter of the United Nations, Article1 paragraph (1) of the Covenant on Civil and Political Rights and the Covenanton Economic, Social and Cultural Rights. Besides that it is also regulated inGeneral Assembly Resolution Number 1514 (XV) 1960, Resolution Number 1541(XV) 1960, and Resolution Number 2625 (XXV) 1970. By regulating these rightsinto various international legal instruments, each nation has the right todetermine selfishness. People which is currently demanding their own right todetermine their fate, is the Catalan people who want to secede from Spain and theKurds who want to separate themselves from Iraq, Iran, Syria and Turkey.There are two rights of self-determination in general, namely in theexternal and internal forms. External self-determination is intended for coloniesand areas that do not have self-government. In its development, some countriesnow prefer internal forms to answer the problem of self-determination, namely inthe form of autonomy. The purpose of writing this thesis is to know the selfdeterminationprinciple in giving the rights of the ethnic groups to determine theirown destiny and to know the implementation of a self-determination principle onethnic groups in the form of internal rights self-determination.From the results of the research it was found that, first the right to selfdeterminationgave the people rights in the form of two rights, namely the right toseparate themselves which was realized through decolonization and the right toself-determination in an internal form. Second, the implementation of selfdeterminationprinciple is realized by providing greater autonomy to the nation orpeople in the region to regulate and manage its territories in pursuit of economic,social and cultural progress and its own form of government. The author'ssuggestion is that in the future the international community will make morespecific arrangements regarding self-determination in an internal form to make iteasier for countries to answer their demands for self-determinationKeyword: The Right to Self-Determination-External Right-Internal Right